Analysis of User Satisfaction Level Of the Online Lecture Information System (Sikuli) using The EUCS Method at Universitas Muhammadiyah Riau - Raihan, Muhammad; Jazman, Muhammad; Ahsyar, Tengku Khairil; Anofrizen, Anofrizen (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The effectiveness of an information system is a key determinant of user pleasure, specifically within digital gaining knowledge of platforms. This studies seeks to evaluate the satisfaction degree of customers towards the the Online Lecture Information System (SIKULI) at Universitas Muhammadiyah Riau, employing the EUCS method. The study similarly investigates the tremendous participants to user satisfaction by using analyzing 5 dimensions from the EUCS making use of a quantitative technique, the studies implemented accidental sampling, related to ninety nine lively college students as respondents. facts evaluation was achieved the use of the SmartPLS software to discover the electricity and course of relationships a number of the variables. The analysis found out that simplest ease of use and timeliness had a statistically tremendous effect on user satisfaction, whereas content, accuracy, and format did not exhibit outstanding effects. those effects emphasize that ease of use and timeliness are key factors in improving satisfaction with SIKULI. consequently, this have a look at offers sensible pointers for technical improvements to optimize the performance of academic information systems.